PARP1 Inhibitor Combined With Oxaliplatin Efficiently Suppresses Oxaliplatin Resistance in Gastric Cancer-Derived Organoids via Homologous Recombination and the Base Excision Repair Pathway - Li, Huafu; Wang, Chunming; Lan, Linxiang; Wu, Wenhui; Evans, Ian; Ruiz, E. Josue; Yan, Leping; Zhou, Zhijun; Oliveira, Joaquim M.; Reis, Rui L.; Hu, Zhenran; Chen, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Oxaliplatin (OXA) resistance in the treatment of different types of cancer is an important and complex problem. The culture of tumor organoids derived from gastric cancer can help us to provide a deeper understanding of the underlying mechanisms that lead to OXA resistance . In this study, our purpose was to understand the mechanisms that lead to OXA resistance, and to provide survival benefits to patients with OXA through targeted combination therapies. Using sequence analysis of OXA-resistant and non-OXA-resistant organoids, we found that PARP1 is an important gene that mediates OXA resistance. Through the patients' follow-up data, it was observed that the expression level of PARP1 was significantly correlated with OXA resistance This was confirmed by genetic manipulation of PARP1 expression in OXA-resistant organoids used in subcutaneous tumor formation. Results further showed that PARP1 mediated OXA resistance by inhibiting the base excision repair pathway. OXA also inhibited homologous recombination by CDK1 activity and importantly made cancer with normal BRCA1 function sensitive to PARP inhibition. As a result, combination of OXA and Olaparib (PARP-1/2/3 inhibitor）, inhibited in vivo and in vitro OXA resistant organoid growth and viability.